Evaluation of the effect of maize-legume intercropping on soil moisture improvement in arid area of Bena-Tsemay district, South omo zone, Southern Ethiopia - Ayele, HM (International Journal of Agricultural Research, Innovation and Technology, 2020)
Usually crop failure due to moisture shortage in soils is very much common due to high evaporation. Sometimes famers try to combat this problem by using mulches of crop residues in the study area. However, this is also highly challenged shortage because the crop residues used as feed for animals. Therefore, using the advantage and opportunity of cover legumes as an intercrop is the solution of the problems simultaneously in addition to their contribution improving soil nutrient balance and other many fold benefits. Therefore, this study aimed for evaluating the effect of maize-legume covers intercropping on soil moisture improvement and crop yield in moisture stress areas of the study area. The entire grain yield of maize and legumes, as well as soil moisture data were collected. The result on soil moisture revealed that intercropping of maize with cowpea had better soil moisture contents during active crop development (15.98%) and after harvest (16.70%) in average as compared to the others. The current finding also showed that adopting intercropping of maize with cowpea-boosted yield by 5256.24 kg ha-1 maize and 977.45 kg ha-1 cowpea in average with higher moisture improvement as compare to the other treatments. Therefore, intercropping of maize with cowpea is important to farmers since it would provide additional crop yield with the same piece of land. However, to get considerable changes on soil and water balances, other soil physic-chemical properties and crop yields, conducting similar studies in more than two years period at permanent field plots is paramount in the future. Int. J. Agril. Res. Innov. Tech. 10(1): 80-86, June 2020